Characterization and evaluation Typha domingensis Pers.) of a fungal growth medium composed pollens powder of cattail ( - Al-Bader, Salah M. (Innovaciencia, 2019)
Introduction: A great progressing occurs in microbiology Ulocladium sp. after culture media have been used in culturing, isolation, identification, and reservation of microorganisms. According to their components, culture media were divided into natural, synthetic, and semisynthetic, the natural medium contain almost all the nutritional requirements but in non-defined quantities. In the current work, the validity of Typha domingensis pollens as a new substrate for fungal culture medium was tested. Several physical and chemical characteristics of medium were detected. The growth of nine fungal isolates were evaluated on semisolid and broth media. Materials and Methods: Ten gram of starchy powder free from spike tissue + 15gm agar were used for one liter of Typha pollens agar (TPA). The growth of local isolates of Candida sp., Rhodotorula sp., Aspergillus niger, , Cladosporium sp., Trichoderma sp., Penicillium sp., Chrysosporium sp., and Microsporum sp. were tested on (TPA), and (PCA). Biomass of filamentous isolates was estimated by TP broth and PC broth.ANOVA test at level 0.05 was followed to clarify the significant increasing of biomass. To qualify the nutritional value of Typha pollens, the percentage oftotal nitrogen , carbon , phosphorus , and potassium were estimated . pH of TPA were detected as well as its color, transparency , and gelatin texture were practically evaluated . Results and Discussion : The chemical composition analysis showed that pollens powder contain C=58%, N=2.16%, P= 0.19%and K=3.36%. The pH was 6.72 at room temperature . Typha pollens agar support growth of all tested fungal isolates. The semisolid TPA had a typical characteristic for culturing and diagnosis of fungi including a suitable gelatin texture and a pale transparent yellow color . All tested fungi except Penicilliumsp. showed higher growth on TPA , on the other side the fungal biomass increased significantly by TP broth in comparison with PC broth (ANOVA test at 0.05 level). Conclusions : Pollens of cattail (T. domingensis ) provide a suitable environment , and nutritive requirements for fungi .It can be usedeasily and successfully as essential substrate for preparing culture medium for primary isolation of fungi. A farther studies were needed to gain a view about using T.domingensis pollens to isolate pathogenic fungi and bacteria.
Keywords: Typha, Cattail, pollen, medium, fungi.